1991
DOI: 10.1007/bf01236049
|View full text |Cite
|
Sign up to set email alerts
|

Morphological patterns in the developing vertebrate retina

Abstract: Changes in the morphology of the early optic cup were observed in embryos of two distantly-related vertebrate species, a teleost fish, northern pike (Esox lucius), and chicken (Gallus gallus). A similar morphological pattern was noted to appear in both species shortly after the involution of the optic vesicle and the formation of the inner retinal layer. At a gross level, three notches were observed in the retinal margin at approximately nasal, dorsal, and temporal positions, while in histological sections a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Given the comparable phenotype despite opposite orientation seen in superior coloboma patients, we hypothesized a similar etiology. Although the standard model of eye development describes an uninterrupted dorsal retina, two older studies of fish eye development identified a groove present in this space [ 18 , 19 ]. To determine if such a structure exists broadly across vertebrates and whether it is a Laminin-lined space, we chose to revisit the study of dorsal eye morphogenesis in fish, chick and mouse.…”
Section: Resultsmentioning
confidence: 99%
“…Given the comparable phenotype despite opposite orientation seen in superior coloboma patients, we hypothesized a similar etiology. Although the standard model of eye development describes an uninterrupted dorsal retina, two older studies of fish eye development identified a groove present in this space [ 18 , 19 ]. To determine if such a structure exists broadly across vertebrates and whether it is a Laminin-lined space, we chose to revisit the study of dorsal eye morphogenesis in fish, chick and mouse.…”
Section: Resultsmentioning
confidence: 99%
“…In a process analogous to that seen for pattern formation in other parts of the embryo, a two-dimensional coordinate system appears to be set up relatively early, before optic cup formation (Crossland et al, 1974;Dutting and Thanos, 1995). Morphologically, notches have been described that delineate nasal, dorsal, and temporal positions early in development and suggest that the retina shows segmentation patterns analogous to other parts of the CNS (Nordquist and McLoon, 1991). The restricted expression patterns of segmentation genes Paiu2 ventrally (Nornes et al, 1990) and Writ-7b dorsally (Parr et al, 1993) support this hypothesis.…”
mentioning
confidence: 89%
“…The apical aspect of the retinal epithelium contains progenitor cells that proliferate and generate the neurons and glia of the neural retina (Nordquist and McLoon, 1991). Neurogenesis begins in the central retina and progresses to more peripheral regions over the course of several days (Mey and Thanos, 1992).…”
Section: Retinal Development and Rxr␥ Gene Expressionmentioning
confidence: 99%